PENGARUH PENDEKATAN RESOURCE BASED LEARNING TERHADAP KEMAMPUAN PENALARAN DAN PEMBUKTIAN MATEMATIS SISWA KELAS X MIPA SMA NEGERI 1 WONOMULYO - Fatimah Fatimah; Herlina Ahmad; Nurlyana Nurlyana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research is experimental research that is motivated by the low ability of reasoning and mathematical proof in class X MIPA of SMA Negeri 1 Wonomulyo. This research aims to determine the effect of the Resource-Based learning approach on students' ability in proofing and mathematical reasoning. It involved two classes that were subjected to different treatments, in the form of mathematics learning with Resource-Based Learning Approach in class X MIPA 1  and mathematics learning without Resource-Based Learning Approach in X MIPA 2. The research instruments used were tests of mathematical reasoning and proofing skills. The results showed that the pre-test means value in the experimental class was 54.81, with a standard deviation 22.802, and in the control class the mean value was 43.31, with a standard deviation 24.526. Meanwhile, the mean value of the post-test results of mathematical reasoning and proofing abilities in the experimental class was 78.64 with a standard deviation 11.514 and in the control class, the mean value was 67.33 with a standard deviation 17.767. The normality test and homogeneity test in both classes obtained data were normally distributed and homogeneous. Based on the hypothesis test, the sig value is obtained 0.001 <0.05 so that H0 is rejected and H1 is accepted or in other words, there is a difference between the experimental class and the control class. It can be concluded that the application of the Resource-Based Learning Approach affects the mathematical reasoning and proofing abilities of students in class.